Phonological Variation in Cirebon Javanese: A Geolinguistic Perspective - Juwintan Juwintan; Eri Kurniawan; R. Dian Dia-an Muniroh (MASI Mandiri Edukasi, 2025)
This research examines Cirebon Javanese phonological variation from a geolinguistic perspective, highlighting the lack of in-depth studies on its phonological structure compared to other Javanese dialects. The aim is to delineate and characterise systematic vowel, consonant, elision, and epenthesis variation across geographical and social settings. Using a descriptive qualitative methodology, data were gathered using the Swadesh list from native informants in 267 villages of the Cirebon regency, which comprised a diverse range of social and geographical settings. The data thus obtained were phonetically transcribed and subsequently analysed through a programmed algorithm that sorted phonological differences. The findings demonstrate the presence of systematic vowel shifts (e.g., /a/ → /ɔ/, /i/ → /ə/), consonant alternations (e.g., /b/ ↔ /w/), as well as elision and epenthesis. The above variations are due to internal linguistic factors, such as syllable structure and stress patterns, as well as external sociolinguistic and geographical considerations. The impact is especially marked in the transitional dialect areas with hybrid phonological characteristics due to language contact and social identity dynamics. This study enhances insight into the phonological variation and evolution in multilingual and dialect-diverse areas.